Análise multicritério aplicada à modelagem da decisão de compra de petróleo - Cruz, Rodrigo Mendonça (2007)
It is of common knowledge that the oil is one of the most valued products in the current days. Therefore it can be said that any improvement in the purchase process means a great increase in the results of any company. This work has as main problem the application of the Multicriteria Decision Method in the decision of purchase of imported oil, which consider aspects of valuation of the product and the supplier. The used method was ELECTRE TRI that is a method of commanded classification where the alternatives are divide in groups following a preview standards. For application of this method, it was necessary to develop some basic concepts to understand the problem like the value concept, information about the petroleum industry and definitions of what it is oil, the main units of refining and the main techniques of valuation of oil. Following the application of Multicriteria Methods, this work presents the comparative analyzes between the results of the application of Multicriteria Methods and the PLANAB, that is the program used for the Petrobras nowadays to measure the values of the oil